2022
DOI: 10.1097/md.0000000000031614
|View full text |Cite
|
Sign up to set email alerts
|

A new predictive tool consolidating CURB-65 with procalcitonin and albumin to assess short-term mortality in hospitalized elderly patients with infectious disease: A retrospective study of a patient cohort

Abstract: Background: Hospitalized elderly patients are often at risk of life-threatening infectious diseases such as pneumonia and urinary tract infection, thus diagnostic tools for bacterial infections are demanded. We developed a new predictive tool consolidating modified CURB-65, procalcitonin (PCT) and albumin (Alb). Method: This is a retrospective study. Modified CURB-65 (mCURB-65) score, PCT, Alb, and various cardiovascular/respiratory/renal functions were measured. Survival analyses were conducted to assess 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Decreased albumin levels are associated with an increased risk of acute respiratory failure and increased frequency of mechanical ventilation [53]. An association of albumin with mortality was also found in other studies; in COVID-19 patients [54], hip fracture patients [55,56], patients with infectious diseases [57], newborn patients [58], the lactate-to-albumin ratio in patients with acute myocardial infarction [59], the albumin-bilirubin score in patients with hypertrophic cardiomyopathy [60], a combined index of hemoglobin, albumin, lymphocyte, and platelet in patients with acute exacerbations of chronic obstructive pulmonary disease [61], and the albumin-to-prealbumin ratio in hemodialysis patients [62]. In malnourished patients, atrophy of the diaphragmatic muscle and loss of muscle mass can occur, in addition to a deterioration of the immune response, which leads to an increased risk of pneumonia.…”
Section: Discussionsupporting
confidence: 58%
“…Decreased albumin levels are associated with an increased risk of acute respiratory failure and increased frequency of mechanical ventilation [53]. An association of albumin with mortality was also found in other studies; in COVID-19 patients [54], hip fracture patients [55,56], patients with infectious diseases [57], newborn patients [58], the lactate-to-albumin ratio in patients with acute myocardial infarction [59], the albumin-bilirubin score in patients with hypertrophic cardiomyopathy [60], a combined index of hemoglobin, albumin, lymphocyte, and platelet in patients with acute exacerbations of chronic obstructive pulmonary disease [61], and the albumin-to-prealbumin ratio in hemodialysis patients [62]. In malnourished patients, atrophy of the diaphragmatic muscle and loss of muscle mass can occur, in addition to a deterioration of the immune response, which leads to an increased risk of pneumonia.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast, the CURB-65 score has poorer specificity in older adults, and adding the “age of above/below 65” criterion to CURB does not increase its sensitivity or specificity in hospitalized patients [ 29 ]. CURB-65 was modified to CURB-age [ 11 ], expanded CURB-65 [ 30 ], and modified CURB-65 [ 31 ] for better prognostic performance. During the COVID-19 pandemic, CURB-65 was used as a prognostic predictor.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 We previously reported that the combination of PCT and Alb can predict 30-day mortality. 10 A number of biomarkers associated with heart failure have also been well recognized, and measuring their concentrations in circulation can be a convenient and noninvasive approach to provide important information about disease severity, and helps in the detection, diagnosis, prognosis and management of heart failure, including PCT, brain natriuretic peptide (BNP) and others. 11 PCT concentrations >2 ng/mL are frequently found in cardiogenic shock patients with multiple organ failure, but a PCT concentration of ≥10 ng/mL seems to be more appropriate for diagnosing this complication in cardiogenic shock patients than 2 ng/mL, which suggests that PCT can be a predictive biomarker not only for infectious disease, but also for prediction of prognosis of shock patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to PCT, albumin (Alb) has also been known to be one of the risk factors for bacterial infectious diseases, such as surgical site infection and aspiration pneumonia 8,9 . We previously reported that the combination of PCT and Alb can predict 30‐day mortality 10 …”
Section: Introductionmentioning
confidence: 99%